NECESSITY FOR ACCESS TO JUSTICE FOR THOSE WHO HAVE NOT WON A COMPETITION UNDER THE BULGARIAN LABOR LAW - Lazarova, Nikoleta (Revista Inclusiones, 2020)
The competition is one of the grounds for the emergence of an employment relationship under the Bulgarian labor legislation. The widespread application of competitive tendering has led to an increase in labor disputes, which are related to the litigation of the legality of the competitive procedures conducted. Practice has shown that in such disputes the unsuccessful candidates do not have access to the court, which is a material violation of their basic right to a fair trial. The reason for the existing legal absurdity is the lack of explicit legal regulation governing judicial control over the legality of the competitions held. On the basis of the conducted research, the conclusion was drawn about the necessity of creating an explicit de lege ferenda provision, which regulates the legal possibility for unsuccessful candidates to challenge the lawfulness of a competition held.